Identification of antidiabetic inhibitors from Allophylus villosus and Mycetia sinensis by targeting α-glucosidase and PPAR-γ: In-vitro, in-vivo, and computational evidence - Md Nur Kabidul Azam; Partha Biswas; Md. Mohaimenul Islam Tareq; Md Ridoy Hossain; Shabana Bibi; Md. Anisul Hoque; Amia khandker; Md Ashraful Alam; Md. Nazmul Hasan Zilani; Mohammad Shahedur Rahman; Norah A. Albekairi; Abdulrahman Alshammari; et al. (Elsevier, 2024)
Diabetes mellitus (DM) is a metabolic disorder arising from insulin deficiency and defectiveness of the insulin receptor functioning on transcription factor where the body loses control to regulate glucose metabolism in β-cells, pancreatic and liver tissues to homeostat glucose level. Mainstream medicines used for DM are incapable of restoring normal glucose homeostasis and have side effects where medicinal plant-derived medicine administrations have been claimed to cure diabetes or at least alleviate the significant symptoms and progression of the disease by the traditional practitioners. This study focused on screening phytocompounds and their pharmacological effects on anti-hyperglycemia on Swiss Albino mice of n-hexane, ethyl acetate, and ethanol extract of both plants Mycetia sinensis and Allophylus villosus as well as the in-silico investigations. Qualitative screening of phytochemicals and total phenolic and flavonoid content estimation were performed significantly in vitro analysis. FTIR and GC-MS analysis précised the functional groups and phytochemical investigations where FTIR scanned 14, 23 & 17 peaks in n-hexane, ethyl acetate, and ethanol extracts of Mycetia sinensis whereas the n-hexane, ethyl acetate, and ethanol extracts of Allophylus villosus scanned 11 peaks, 18 peaks, and 29 peaks, respectively. In GC-MS, 24 chemicals were identified in Mycetia sinensis extracts, whereas 19 were identified in Allophylus villosus extracts. Moreover, both plants' ethyl acetate and ethanol fractioned extracts were reported significantly (p < 0.05) with concentrations of 250 mg and 500 mg on mice for oral glucose tolerance test, serum creatinine test and serum alkaline phosphatase test. In In silico study, a molecular docking study was done on these 43 phytocompounds identified from Mycetia sinensis and Allophylus villosus to identify their binding affinity to the target Alpha Glucosidase (AG) and Peroxisome proliferator-activated receptor gamma protein (PPARG). Therefore, ADMET (absorption, distribution, metabolism, excretion, and toxicity) analysis, quantum mechanics-based DFT (density-functional theory), and molecular dynamics simulation were done to assess the effectiveness of the selected phytocompounds. According to the results, phytocompounds such as 2,4-Dit-butyl phenyl 5-hydroxypentanoate and Diazo acetic acid (1S,2S,5R)-2-isopropyl-5-methylcyclohexyl obtained from Mycetia sinensis and Allophylus villosus extract possess excellent antidiabetic activities.